Adult-onset CNS myelin sulfatide deficiency is sufficient to cause Alzheimer’s disease-like neuroinflammation and cognitive impairment - Shulan Qiu (Molecular Neurodegeneration, 2021)
Abstract Background Human genetic association studies point to immune response and lipid metabolism, in addition to amyloid-beta (Aβ) and tau, as major pathways in Alzheimer’s disease (AD) etiology. Accumulating evidence suggests that chronic neuroinflammation, mainly mediated by microglia and astrocytes, plays a causative role in neurodegeneration in AD. Our group and others have reported early and dramatic losses of brain sulfatide in AD cases and animal models that are mediated by ApoE in an isoform-dependent manner and accelerated by Aβ accumulation. To date, it remains unclear if changes in specific brain lipids are sufficient to drive AD-related pathology. Methods To study the consequences of CNS sulfatide deficiency and gain insights into the underlying mechanisms, we developed a novel mouse model of adult-onset myelin sulfatide deficiency, i.e., tamoxifen-inducible myelinating glia-specific cerebroside sulfotransferase (CST) conditional knockout mice (CSTfl/fl/Plp1-CreERT), took advantage of constitutive CST knockout mice (CST−/−), and generated CST/ApoE double knockout mice (CST−/−/ApoE−/−), and assessed these mice using a broad range of methodologies including lipidomics, RNA profiling, behavioral testing, PLX3397-mediated microglia depletion, mass spectrometry (MS) imaging, immunofluorescence, electron microscopy, and Western blot. Results We found that mild central nervous system (CNS) sulfatide losses within myelinating cells are sufficient to activate disease-associated microglia and astrocytes, and to increase the expression of AD risk genes (e.g., Apoe, Trem2, Cd33, and Mmp12), as well as previously established causal regulators of the immune/microglia network in late-onset AD (e.g., Tyrobp, Dock, and Fcerg1), leading to chronic AD-like neuroinflammation and mild cognitive impairment. Notably, neuroinflammation and mild cognitive impairment showed gender differences, being more pronounced in females than males. Subsequent mechanistic studies demonstrated that although CNS sulfatide losses led to ApoE upregulation, genetically-induced myelin sulfatide deficiency led to neuroinflammation independently of ApoE. These results, together with our previous studies (sulfatide deficiency in the context of AD is mediated by ApoE and accelerated by Aβ accumulation) placed both Aβ and ApoE upstream of sulfatide deficiency-induced neuroinflammation, and suggested a positive feedback loop where sulfatide losses may be amplified by increased ApoE expression. We also demonstrated that CNS sulfatide deficiency-induced astrogliosis and ApoE upregulation are not secondary to microgliosis, and that astrogliosis and microgliosis seem to be driven by activation of STAT3 and PU.1/Spi1 transcription factors, respectively. Conclusion Our results strongly suggest that sulfatide deficiency is an important contributor and driver of neuroinflammation and mild cognitive impairment in AD pathology.